Vertical integration and investor protection in developing countries - Rocco Macchiavello (Fondazione Eni Enrico Mattei (FEEM), 2009)
The industrial organization of developing countries is characterized by the pervasive use of subcontracting arrangements among small, financially constrained firms. This paper asks whether vertical integration relaxes those financial constraints. It shows that vertical integration trades off the benefits of joint liability against the costs of rendering the supply chain more opaque to external investors. In contrast to the commonly held view that pervasive input and capital market imperfections are conducive to vertical integration, the model predicts that the motives for vertical integration are not necessarily higher in developing countries. In particular, vertical integration is more likely to arise at intermediate levels of investor protection and better contract enforcement with suppliers reduces vertical integration only if financial markets are sufficiently developed. Evidence supporting both predictions is discussed.
Keywords: O12; O16; D23; G30; L22; 330; Vertical Integration; Industrial Development; Financial Constraints; Joint Liability; Trade Credit; Community-based Industries